Sensitivity and specificity for African horse sickness antibodies detection using monovalent and polyvalent vaccine antigen-based dot blotting - Machimaporn Taesuji; Khate Rattanamas; Usakorn Kulthonggate; Thanongsak Mamom; Sakchai Ruenphet (Veterinary World, 2022)
Background and Aim: The immune responses of animals infected with African horse sickness (AHS) virus are determined by enzyme-linked immunosorbent assay (ELISA), complement fixation, and virus neutralization test. During the outbreaks of AHS in Thailand, the immune response after vaccination has been monitored using commercial test kits such as blocking ELISA, which are expensive imported products unavailable commercially in Thailand. This study aimed to assess the sensitivity and specificity of anti-AHS virus antibodies using dot blotting based on monovalent and polyvalent strains of live attenuated AHS vaccine.